Gambaran Motivasi Belajar Pada Remaja Yang Mengalami Broken Home Dampak Perceraian Orang Tua Di SMA Laboratorium UM Kota Malang - Tesalonika Liontinia Crossesa; Goretti Maria Sindarti (Poltekkes Kemenkes Malang, 2019)
Prolonged conflicts in the family will result in divorce. In this case the divorce that occurs will have an adverse effect on the child. Not only the emotional and psychological problems in the child will be disrupted but the problem of learning motivation in the child will also decrease. The purpose of this study was to determine the picture of learning motivation in adolescents who experienced Broken Home or the impact of divorce parents. This research is a descriptive case study with 2 research subjects and was conducted on March 12, 2019. This study uses in depth interviewing techniques in data collection with prepared instruments. Data is presented in narrative form. The results showed that both research subjects namely BA and FH, both still had the motivation to learn even though in the circumstances of divorced parents, the motivation of the two research subjects was obtained from the support of their loved ones. The recommendation for further research is that researchers should be able to build warmer and deeper relationships with subjects who will be respondents in the study